Review - Muruti, Gopinath; Hawa Mokhtar, Siti; Abdul Rahim, Fiza; Ibrahim, Zul-Azri; M. Al-Ghaili, Abbas (International Journal of Engineering and Technology, 2018)
Forensics is a vital point for law enforcement, civil litigators, and different experts who manage complex advanced examinations. Digital forensics has assumed a noteworthy part in a portion of the biggest criminal and civil investigations. However, the ascent in the prevalence of big data as a better approach for unraveling the challenges exhibited by huge, complex data due to the progression of innovations such as the Internet, Internet of Things (IoT), and Cloud Computing. These challenges have contributed to data deluge and forensics tool limitations in the digital forensics investigation. In this paper, a number of challenges faced by the digital forensics investigator in a big data environment are discussed. The identified challenges could significantly contribute to a more efficient digital forensics process in the big data environment.Â